A rare case of bladder chondroma - Carter, Michael D.; Rendon, Ricardo A.; Merrimen, Jennifer (Canadian Urological Association Journal, 2015)
Soft tissue chondromas are benign tumours that arise commonly in the hands and feet of adults, but rarely in other locations. Only two prior cases of chondroma of the urinary bladder wall have been reported. We describe a third case and discuss similarities and differences between the three cases reported to date.